A qualitative examination of the decision‐making process of simultaneous alcohol and cannabis use: Intentions and willingness. (8th December 2022) - Boyle, Holly K.; Singh, Samyukta; López, Gabriela; Carey, Kate B.; Jackson, Kristina M.; Merrill, Jennifer E.
Abstract: Background: Alcohol and cannabis use are common among young adults and most young adults who use both substances have used them simultaneously (i.e., using both substances so their effects overlap). Because simultaneous use is associated with a greater number and severity of consequences than single substance use, research is needed to examine the decision‐making process of engaging in this high‐risk behavior. We conducted a qualitative examination of intentions (i.e., plans) and willingness (i.e., one's openness to engage in the behavior if an opportunity presents itself) to engage in simultaneous use from the perspective of young adults who frequently report this substance use behavior. Methods: We recruited 36 young adults who reported simultaneous use and heavy drinking (4+/5+ drinks for women/men; 64% women, ages 18 to 25) to participate in semi‐structured interviews. All interviews were double coded for thematic analysis and both novel and a priori themes were found. Results: Young adults distinguished between intending to engage in simultaneous use and being willing to engage in simultaneous use. They reported that intentions and willingness varied from occasion to occasion. They also reported that context and alcohol consumption influenced their willingness to engage in simultaneous use. Peer pressure or offers increased their willingness to use cannabis while drinking and having current or next‐day responsibilities decreased their willingness to engage in simultaneous use. Additionally, planned simultaneous use occasions were characterized as being special events where young adults consumed more substances, but were more likely to monitor their use than unplanned occasions. Conclusions: Intentions and willingness may be important proximal predictors of simultaneous use of alcohol and cannabis. Building off this qualitative work, quantitative research should identify which factors influence the decision‐making process to engage in simultaneous use and determine when intentions and willingness are most predictive of risky simultaneous use behavior. Abstract : Individual interviews were conducted to understand young adults' decision‐making surrounding simultaneous alcohol and cannabis use. Findings suggest intentions and willingness to engage in simultaneous use varied across and during substance use occasions. Participants reported physical and social context, current and next day responsibilities, and level of alcohol consumption influenced willingness to engage in simultaneous use. Additionally, planned simultaneous use occasions were characterized as special events with increased substance use, but with more monitoring of use than unplanned occasions.